2010
DOI: 10.1007/s11069-010-9585-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of satellite-based rainfall estimates in urban areas in different geographic and climatic regions

Abstract: This paper presents an assessment of the 3B42 research version rainfall product from NASA's Tropical Rainfall Measuring Mission Multi-satellite Precipitation Analysis (TMPA). The study provides new results of TMPA data accuracy in urban areas and highlights trends associated with the climatological indicators of temperature and relative humidity in cities. Ten years (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007) of TMPA data were analyzed for three case study cities in the United States (Houston,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…However, in this study, the error distribution characteristics of satellite-based rainfall products are not discussed further. Han et al [9] also evaluated the accuracy of TRMM data in urban areas in different climatic regions (Houston, Atlanta, Las Vegas in the United States and one in Korea, Cheongju), as a function of climatic variables, and for different storm types. The results show that the relative magnitude of TRMM rain accumulation compared to rain gauge accumulation is smaller for higher rainfall intensity events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in this study, the error distribution characteristics of satellite-based rainfall products are not discussed further. Han et al [9] also evaluated the accuracy of TRMM data in urban areas in different climatic regions (Houston, Atlanta, Las Vegas in the United States and one in Korea, Cheongju), as a function of climatic variables, and for different storm types. The results show that the relative magnitude of TRMM rain accumulation compared to rain gauge accumulation is smaller for higher rainfall intensity events.…”
Section: Discussionmentioning
confidence: 99%
“…Different rainfall trends have been observed from many discrete ground meteorological stations [7]. However, those studies are limited in terms of both their sparse spatial scope and data accuracy [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cold cloud duration (CCD) can be derived from Meteosat thermal IR imaging (Dugdale et al, 1991) and provides rainfall estimates based on the length of time a cloud top is below a threshold temperature. The Tropical Rainfall Measuring Mission (TRMM; http://trmm.gsfc.nasa.gov/) satellite provides near-real-time direct measurement of rainfall in tropical areas based on passive microwave and active radar sensors, which closely matches ground rain gage observations (Sharma et al, 2007;Han et al, 2010), even in urban areas (Hand and Shepherd, 2009). Nevertheless, the influence of location, climate, topography, time period, cloud types and rainfall types can affect accuracy (Barros et al, 2000).…”
Section: Rainfallmentioning
confidence: 99%
“…They also referred to taking into consideration limitations regarding both the accuracy of the TRMM and the interpolation process of the E-OBS datasets. Han et al (2011) studied the assessment of the accuracy of satellite-based rainfall data in urban areas in different climatic regions, as a function of climatic variables, and for different storm types. They found that satellite-based rainfall data matched well with rain gauge observations at all locations, while a possible linkage between the observed urbanmodified temperatures, hypothesized enhanced convection and improved satellite-based rainfall data accuracy existed in urban areas.…”
Section: Introductionmentioning
confidence: 99%